Anxiety and Shame as Risk Factors for Depression, Suicidality, and Functional Impairment in Body Dysmorphic Disorder and Obsessive Compulsive Disorder. Issue 11 (November 2016) - Weingarden, Hilary; Renshaw, Keith D.; Wilhelm, Sabine; Tangney, June P.; DiMauro, Jennifer
Abstract : Abstract: Body dysmorphic disorder (BDD) and obsessive compulsive disorder (OCD) are associated with elevated depression, suicidality, functional impairment, and days housebound, yet little research has identified risk factors for these outcomes. Using path analysis, the present study examined anxiety and shame as risk factors for these outcomes across Internet-recruited self-report groups (BDD [ n = 114], OCD [ n = 114], and healthy control [HC; n = 133]). Paths from anxiety and shame to outcomes were similar and mostly significant across BDD and OCD, compared to non-significant paths for HCs, with one exception: the path from shame to depression was significant in the BDD group ( b = 0.32) but non-significant in the OCD group ( b = 0.07). Findings underscore similarities in BDD and OCD, supporting their reclassification into the same Obsessive Compulsive Related Disorders category. Results emphasize the importance of targeting shame, in addition to anxiety, in treatments for BDD and OCD.